A Method of Quantifying Refrigerant Distribution in a Two-Pass Micro-Channel Evaporator - Xu, Geng; Chen, Hua; Zhao, Songtian; Ren, Shusong; Zhao, Wei (Recent Patents on Mechanical Engineering, 2022)
Background: The flow rate distribution in the flat tubes of a micro-channel evaporator is essential for its heat transfer performance. Due to a large number of flat tubes in a microchannel evaporator, the flow rate distribution is often difficult to determine. Objective: An evaporator test rig was constructed to study the quantification of the refrigerant mass flow rate distribution in a two-pass evaporator without destroying its structure. Methods: A heat transfer performance test rig for a two-pass evaporator was utilized. Subcooled refrigerant R134a was pumped into the inlet header, and infrared thermography was used to obtain the cloud map of the wall temperature distribution on the surface of the evaporator. The flow rate distribution in each flat tube was calculated based on an analysis that combines the heat balance between the air side and the refrigerant side with the effectiveness-Number of Transfer Units (ε- NTU) method. Results: The flow rate distribution was found to be in good agreement with the evaporator wall temperature distribution. The difference between the calculated and measured total mass flow rates was less than 15.9%, which proves that the method is simple and effective. And the unevenness of flow rate distribution in the 1st and 2nd pass is 0.13 and 0.32, respectively. Conclusion: This method is simple and effective, and does not destroy the structure of the microchannel evaporator. However, it is only suitable for cases in which there exists a subcooled zone in a pass, and is not applicable to a pass in which the refrigerant is only in a single-phase or a two-phase state.
Keywords: two-phase flow